AMBULATORY ARTERIAL STIFFNESS INDEX PREDICTS CARDIOVASCULAR EVENTS IN PATIENTS WITH NON-ST ELEVATION MYOCARDIAL INFARCTION: ONE-YEAR FOLLOW-UP STUDY. (April 2021) - Koumelli, A.; Tsioufis, K.; Kouremeti, M.; Mantzouranis, M.; Konstantinou, K.; Vogiatzakis, N.; Tolis, P.; Tolis, E.; Leontsinis, I.; Tousoulis, D.
Abstract: Objective: Ambulatory arterial stiffness index (AASI) has been shown to predict cardiovascular morbidity and mortality in hypertensive patients. However, there are limited data with respect to its prognostic significance among patients with acute myocardial infarction (AMI). Weevaluated the relationship between AASI and long-term cardiovascular outcomes in patients withAMI. Design and method: We followed up 254patients (82.7% male; mean age 63.7 years; 71.7% hypertensives; 29.9% with diabetes mellitus) who were hospitalized because of ST-elevation MI (STEMI, 48.8%) and Non-ST–elevation MI (NSTEMI), for a period of 12 months. All patients underwent baseline estimation of clinical and laboratory parameters during their hospitalization. Patients underwent 24-hour ambulatory blood pressuremonitoring (ABPM) during the third day of hospital stay. The AASI was calculated as 1- (slope of diastolic on systolic blood pressureduring ABPM). Endpoints of interest where total and cardiovascular mortalityand cardiovascular morbidity set as hospitalization for congestive heart failure, acute coronary syndrome, stroke, ventricular tachycardia, atrial fibrillation and acute renal failure. Results: The AASI failed to predict mortality orthe composite endpoint of cardiovascular morbidity and mortality during the follow-up period either in the entire population or separately for each AMI type. However, AASI demonstrated a significant prognostic role for hospitalization for cardiovascular events in the NSTEMI population in univariate regression analysis (HR = 0.102; 95% CI: 0.048–0.155; p < 0.001). In a model of multivariate regression analysis in the same AMI group, this association was maintained (HR = 0.067; 95% CI: 0.020–0.115; p = 0.006) after adjusting for traditional risk factors and severity of coronary artery disease assessed by the number of affected main vessels. Conclusions: AASI emerges as an independent predictor of one-year cardiovascular morbidity in patients with NSTEMI. More data are required to determine the usefulness of this non-invasive tool in risk stratification and management of these patients.